(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2017)
The first article discusses a current concern in religious tolerance and interfaith relationship. Based on a study of Chinese Muslim converts in Terengganu in Malaysia, the authors discuss the extent to which the community adheres to the framework of the 'dialogue of life', a form of religious discourse which is in line with the Islamic wisdom of interfaith tolerance practices, in their everyday relationship with Muslims and non-Muslims.